2013
DOI: 10.1021/ml400197u
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Property Based Design of Pyrazolo[1,5-a]pyrimidine Inhibitors of CK2 Kinase with Activity in Vivo

Abstract: In this letter, we describe the design, synthesis, and structure−activity relationship of 5-anilinopyrazolo [1,5-a]pyrimidine inhibitors of CK2 kinase. Property-based optimization of early leads using the 7-oxetan-3-yl amino group led to a series of matched molecular pairs with lower lipophilicity, decreased affinity for human plasma proteins, and reduced binding to the hERG ion channel. Agents in this study were shown to modulate pAKT S129 , a direct substrate of CK2, in vitro and in vivo, and exhibited tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 14 publications
3
47
0
Order By: Relevance
“…Alternative 3-aryl-oxetan-3-ol substrates were prepared (5-10), each with a para-donating aromatic groups (see the Supporting Information). Using either catecholo r2 -methylphenol gave the desired oxetane products in each case (11)(12)(13)(14)i n3 3-77 %y ields. Importantly,h eterocyclesw ere also suitable as the preinstalled aromatic group.2 -Methylfuran was capable of stabilizing the carbocationic intermediate affording oxetane 15 in 58 %y ield, providing another functionalizable handle.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Alternative 3-aryl-oxetan-3-ol substrates were prepared (5-10), each with a para-donating aromatic groups (see the Supporting Information). Using either catecholo r2 -methylphenol gave the desired oxetane products in each case (11)(12)(13)(14)i n3 3-77 %y ields. Importantly,h eterocyclesw ere also suitable as the preinstalled aromatic group.2 -Methylfuran was capable of stabilizing the carbocationic intermediate affording oxetane 15 in 58 %y ield, providing another functionalizable handle.…”
Section: Resultsmentioning
confidence: 95%
“…[11,12] In drug discovery settings, the incorporation of the polar,l ow molecular weighto xetane moiety has often afforded compounds with enhanced properties such as improved metabolic stability, solubility and lipophilicity. [13] As part of our interest in the synthesis of novel oxetane derivatives, [14] we were intrigued by possible approaches to 3,3-diaryloxetanes, designedt op rovide isosteres for diarylketonea nd diarylmethanes tructures with improvedp roperties ford rug discovery.A tt he outset of this work, there were no reported examples of disubstituted 3,3-diaryloxetanesi nt he literature. [15,16] Indeed,i nternal efforts within Pfizer corroborated this observation, with this motif being recognized as difficult to access.…”
Section: Introductionmentioning
confidence: 99%
“…Dowling et al 81 at AstraZeneca compared 3-aminooxetane motifs with other small rings through a series of matched pairs ( Figure 9). It was found that introduction of oxetane lowered logD by ∼0.8 unit in comparison to aminocyclopropane and aminocyclobutane derivatives.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Incorporation of an oxetane resulted in the greatest improvement in metabolic stability and lipophilicity. Overall, 2,4,4- Dowling et al 81 at AstraZeneca described a series of 5anilinopyrazolo[1,5-a]pyrimidine inhibitors of CK2 kinase (Figure 9, section 2). An N-oxetanyl group was used in place of a N-cyclopropyl group to reduce lipophilicity without the introduction of a basic group.…”
Section: Applications In Medicinal Chemistrymentioning
confidence: 99%
“…They further evaluate this series for both mechanistic and phenotypic endpoints, including pAKT levels and antiproliferative activity. [13][14][15][16] While the compounds are potent, even one of their best compounds (17) also has offtargets (HIPK1-4, DAPK1-3, DYRK2, and BMPR1B) that may confound interpretation of biological results. 15 Due to its narrow kinome profile as well as potency, we started our CK2 probe project utilizing this promising scaffold.…”
mentioning
confidence: 99%